A Case Report and Review of the Literature: Reactive Arthritis Caused by Clostridioides difficile ribotype 027 - Zimmermann, Ortrud; Köchel, Heinrich; Bohne, Wolfgang; Pollok-Kopp, Beatrix; Passenberg, Peter; Groß, Uwe (Frontiers in Microbiology, 2022)
With an annual incidence of 250-300 per 100,000 inhabitants, reactive arthritis is not uncommon. However, the fact that Clostridioides difficile infection (CDI) can also lead to this complication is largely unknown. We report on a 69-years-old man who developed reactive arthritis of his right knee joint one week after antibiotic-associated diarrhea with evidence of C. difficile of the hypervirulent ribotype 027. His female partner also became infected with C. difficile ribotype 027, but did not develop reactive arthritis. The further investigation showed that the patient - in contrast to his partner - was HLA-B27 positive and had strong antibody levels against C. difficile. The case history together with the review of 45 other cases described so far shows that C. difficile can also lead to reactive arthritis. C. difficile-associated reactive arthritis (CDARA) is characterized by the fact that patients suffer from diarrhea or colitis after taking antibiotics, toxigenic C. difficile or only the toxins are detectable in the stool and there are no other explanations for the arthritis and diarrhea.